The Representation of Gender in the Required EFL Textbook of an Indonesian Junior High - Wina Yulistiana; Desy Rusmawaty; Bibit Suhatmady (English Department, Faculty of Teacher Training and Education, Mulawarman University, 2022)
Textbooks are a kind of resource that is often used in the teaching and learning processes in schools by instructors and students. In EFL English textbooks, gender equality becomes a sign of gender discrimination. Consequently, this study assessed the extent to which both sexes were portrayed equally in junior high school English textbooks. The goal of this study is to ascertain how gender is portrayed in EFL textbooks in terms of family responsibilities and employment. To establish the gendering of their dialogues in EFL textbooks. To define the EFL textbook's qualities as determined by junior high schools. To answer the research question, the content analysis method is applied in this research. Each page of the EFL textbook was analyzed to find six aspects. These aspects consist of the six aspects analyzed in the textbook are pictures of women or men, women or men mentioned, roles, games, models, and names of men or boy. The result of this study indicate that in representing gender roles in the EFL textbook “When English Rings a Bell”, the researcher found the results of the overall analysis of the number of female roles more than male roles, namely for the pictures mentioned of gender names, occupation roles, roles domestic, predominantly female play, the roles models conveyed al lead to female characters as seen in the EFL English textbook “When English Rings A Bell”. After conducting the analysis, it can be concluded that the EFL English Textbook contains different levels of gender bias in the exercises in each chapter. Men are dominant in two categories, namely work, and activities. Meanwhile, women only have a dominant number in the visibility category. Overall, textbook authors have tried to promote gender equality in textbooks. Men are still dominant in textbooks. The textbooks in this study still contain issues of gender bias. So it is hoped that it can be revised so that gender representation in all textbooks will be represented equally